The Impact of Media Exposure on the Poetry Writing Skills of Class X Stu-dents: Exploring the Role of the Connecting Motif - Ellison, Dwivedi; Callista, Meiyanti (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
In a digital age where media consumption is ubiquitous, understanding the impact of media exposure on the creative abilities of students is imperative. This research explores the intricate relationship between media exposure and the poetry writing skills of Class X students, focusing on the thematic motif of "connecting" in media content. The study employs a mixed-method approach, combining quantitative assessment of poetry writing skills and qualitative analysis of media content and student interviews. The findings reveal a significant positive correlation between media exposure to content featuring the "connecting" motif and the poetry writing skills of Class X students. Students who engage deeply with such media exhibit higher levels of creativity, vivid imagery, and emotional resonance in their poetry. The study further highlights gender disparities in the influence of media, with female students displaying a more pronounced correlation. These results underscore the potential of media to serve as a catalyst for nurturing creativity in the classroom. They emphasize the importance of media literacy education, curriculum integration, and gender-responsive teaching strategies. The study also calls for further research to delve into the mechanisms governing the relationship between media and creative writing, explore the influence of different media types, cultural factors, and individual characteristics, and conduct longitudinal studies to trace the long-term impact of media exposure on creative abilities.